EFEKTIFITAS METODE PERSONIFIKASI DALAM MENINGKATKAN KEMAMPUAN MEMBACA HURUF HIJAIYAH BAGI ANAK BERKESULITAN BELAJAR X (Single Subject Design Kelas V SDN. 09 Koto Luar Padang) - M. ABD Van Faysa (Universitas Negeri Padang, 2014)
Abstrack: This study aims to test the effectiveness of the use of personification methods in improving reading skills for children hijaiyah class learning difficulties SDN 09 Padang Koto Luar. This research Single Subject Research approach and design of the ABA. Subjects were a student learning difficulties in class V. To measure the research variables, the percentage of the techniques applied. Based on the results of data analysis, it was found that the use of personification effective method to improve reading skills learning disabilities hijaiyah children in class V SDN 09 Padang Koto Luar Kata-kata kunci: Personifiksi; Membaca; Huruf Hijaiyah; Kesulitan Belajar